Chondrodysplasia Punctata - Narang, GS; Arora, S; Khurana, MS; Singh, T; Shifali, Dr (Journal of Nepal Paediatric Society, 2014)
We report a case of two and a half months old male child affected by chondrodysplasia punctata, a rare condition characterized by depressed nasal bridge, hypoplastic distal phalanges and epiphyseal stippling of the bones. DOI: http://dx.doi.org/10.3126/jnps.v34i1.9110 J Nepal Paediatr Soc 2014;34(1):57-61